2013
DOI: 10.1111/nph.12469
|View full text |Cite
|
Sign up to set email alerts
|

Open Stomata 1 (OST1) is limiting in abscisic acid responses of Arabidopsis guard cells

Abstract: SummaryOpen Stomata 1 (OST1) (SnRK2.6 or SRK2E), a serine/threonine protein kinase, is a positive regulator in abscisic acid (ABA)-mediated stomatal response, but OST1-regulation of K + and Ca 2+ currents has not been studied directly in guard cells and it is unknown whether OST1 activity is limiting in ABA-mediated stomatal responses.We employed loss-of-function and gain-of-function approaches to study native ABA responses of Arabidopsis guard cells. We performed stomatal aperture bioassays, patch clamp analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 101 publications
7
145
0
1
Order By: Relevance
“…It is considered that activation, with some dependence on Ca 2+ , of anion channels is a key and early step of the cascade resulting in ABA-triggered stomatal closure (Scherzer et al, 2012). CPK4 may eventually combine its action with that of other guard cell-expressed kinases, like OPEN STOMATA1 (Acharya et al, 2013;Imes et al, 2013) and CPK3/CPK6/CPK21/CPK23 (Mori et al, 2006;Brandt et al, 2012), which have been reported as promoting stomatal closure through their action on anion channels.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that activation, with some dependence on Ca 2+ , of anion channels is a key and early step of the cascade resulting in ABA-triggered stomatal closure (Scherzer et al, 2012). CPK4 may eventually combine its action with that of other guard cell-expressed kinases, like OPEN STOMATA1 (Acharya et al, 2013;Imes et al, 2013) and CPK3/CPK6/CPK21/CPK23 (Mori et al, 2006;Brandt et al, 2012), which have been reported as promoting stomatal closure through their action on anion channels.…”
Section: Resultsmentioning
confidence: 99%
“…The SnRK2-type protein kinase OST1 is one of the major ABA signaling components in guard cells, but it also functions in roots and seeds Mustilli et al, 2002;Yoshida et al, 2002;Xie et al, 2006;Fujita et al, 2009;Acharya et al, 2013). Our goal was to identify OIPs using in planta protein complex isolations followed by LC-MS/MS analyses.…”
Section: Discussion Design and Aba Responses Of Ost1-hf Linesmentioning
confidence: 99%
“…ABA needs to first trigger the production of reactive oxygen species to activate Ca 2+ channels, which mediate the influx of external Ca 2+ to increase the cytosolic Ca 2+ concentration (Pei et al, 2000;Allen et al, 2001Allen et al, , 2002. It has also been reported that KAT1 can be inhibited through phosphorylation by kinases and that the C terminus of KAT1 is the main targeting site for this phosphorylation event (Mori et al, 2000;Sato et al, 2009Sato et al, , 2010Acharya et al, 2013). All these diverse regulators are involved in KAT1 regulation, which may be slow and consume energy.…”
Section: Drought Stress Induces a Significant Upregulation Of The Expmentioning
confidence: 99%